Analysis of trypsin inhibitor-like cysteine-rich domain-containing peptides (TIL-domain inhibitors) from the tick Ixodes ricinus - Pechová, Hana (Jihočeská univerzita, 2021)
The master thesis deals with the analysis of trypsin inhibitor-like cysteine-rich domain-containing peptides (TIL-domain inhibitors) extracted from salivary glands of a tick Ixodes ricinus. It comprises the initial bioinformatical analysis of TIL-domain containing peptide family from I. ricinus, molecular cloning of the representative protein into expression vector, followed by production of recombinant TIL-domain inhibitor in bacteria. A representative TIL-domain gene is proved for their structure, biochemical properties as well as immunomodulatory and anticoagulation features.
Analysis of trypsin inhibitor-like cysteine-rich domain-containing peptides (TIL-domain inhibitors) from the tick Ixodes ricinus
Keywords: trypsin inhibitor-like cysteine-rich domain-containing peptides; TIL-domain inhibitors; Ixodes ricinus; protein expression; purification; anti-protease activity; anticoagulation activity; immunomodulation; trypsin inhibitor-like cysteine-rich domain-containing peptides; TIL-domain inhibitors; Ixodes ricinus; protein expression; purification; anti-protease activity; anticoagulation activity; immunomodulation